Comparison of immunological and immunogenetic markers in recent-onset type 1 diabetes among children and adults - Kristi Alnek; Aili Tagoma; Kaja Metsküla; Ija Talja; Helis Janson; Maire Mandel; Tamara Vorobjova; Astrid Oras; Hanna Sepp; Katrin Pruul; Koit Reimand; Tiia Simonen; et al. (Scientific Reports)
Abstract This study aimed to compare the immunological and immunogenetic profiles over a spectrum of childhood- and adulthood-onset T1D at diagnosis. The cross-sectional study involved participants with recently diagnosed T1D (n = 168), aged 2.9–68.2 years. HLA-II alleles, single nucleotide polymorphisms (SNP) (rs2476601, rs3087243, rs1990760, rs13266634), thyroid and coeliac disease-related autoantibodies and anti-enterovirus antibodies (anti-EV) were analysed regarding the diabetes-associated autoantibodies’ (DAA) status and the age of participants. In the longitudinal study, 19 immune checkpoint gene expression levels in children (n = 25) aged 3.6–14.5 years were measured at diagnosis and 1 year after diagnosis. The duration of symptoms before diagnosis was age-dependent. Older age increased the odds of being single DAA-positive (OR 1.05; 95% CI 1.02–1.09), while anti-EV IgG positivity increased the odds of being multiple DAA-positive (adjusted OR 4.42; 95% CI 1.62–12.04). The DAA-negative T1D participants were older than the DAA-positive individuals. The checkpoint gene expression levels between the two time points were similar, but exhibited more pronounced variability at the time of diagnosis. These results confirm immunological variability in recent-onset T1D cases between children and adults and stress the importance of further research to define the comprehensive immunological profile of the disease age-related subgroups.